La necropoli di Fornaci a Capua. Alcuni contesti inediti dell’Orientalizzante Antico e Medio (ACME, 2021)
This paper focuses on some contexts of the Fornaci necropolis in Capua, excavated between 60s and 80s by W. Johannowsky. The topographic analysis of some parts of the necropolis shows organic and structured depositional forms between the second half of eighth and the half of seventh century BC (Capua IIB-III). The recognition of some groups of tombs centreted around a more ancient one and the characteristic burial methods reserved to acerba graves could suggest a genealogical link among them.